2013
DOI: 10.1002/bit.24853
|View full text |Cite
|
Sign up to set email alerts
|

Remote delivery of hydroxyl radicals via secondary chemistry of a nonthermal plasma effluent

Abstract: Electron paramagnetic resonance spectroscopy is used to observe hydroxyl radicals produced by an atmospheric pressure nonthermal plasma device at distances greater than 1 m from the discharge. The plasma device is an indirect treatment setup with closed loop airflow and hydrogen peroxide additives that is effective in deactivating bacteria on time scales of seconds. The generation of the detected hydroxyl radicals is shown to occur in secondary chemical processes near the point of delivery of the plasma treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Higher humidity of the process gas led to higher inactivation rates and this was attributed to the formation and impact of hydroxyl radicals (Hähnel et al ). However, since the gas‐phase lifetime of hydroxyl radicals is reported to be very short, it is unlikely that hydroxyl radicals created in the discharge reach the target in a remote operation mode when the distance to the treatment site is more than 1 cm (Plimpton et al ). But even though hydroxyl radicals represent a short‐lived species, their contribution to the sporicidal effect cannot be ruled out, since at high humidity, they might be produced by the reaction of the long‐lived species such as ozone with water molecules close to the sample surface (Jeon et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher humidity of the process gas led to higher inactivation rates and this was attributed to the formation and impact of hydroxyl radicals (Hähnel et al ). However, since the gas‐phase lifetime of hydroxyl radicals is reported to be very short, it is unlikely that hydroxyl radicals created in the discharge reach the target in a remote operation mode when the distance to the treatment site is more than 1 cm (Plimpton et al ). But even though hydroxyl radicals represent a short‐lived species, their contribution to the sporicidal effect cannot be ruled out, since at high humidity, they might be produced by the reaction of the long‐lived species such as ozone with water molecules close to the sample surface (Jeon et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Several nonthermal plasma generators display higher levels of hydroxyl radicals, compared with non-water vapor plasma discharges, when supplied with water vapor [18,19,25]. Alteration of the amount of oxygen in the starting plasma, gaseous medium has been shown to affect the amount of nitrogen oxide during association with nitrogen.…”
Section: Plasma Spectra Characteristicsmentioning
confidence: 99%
“…Several recent studies have referenced the use of water vapor in the generation of nonthermal plasma. These studies have identified discharge spectra profiles, composed of elevated hydroxyl radicals and hydrogen peroxide [18,19]. This current paper does not discuss the use of humidified air or water vapor as a source of plasma starting material.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma, a partially ionized gas, has proven to have a broad range of industrial and biomedical applications (Bogaerts et al, ; Chen, ; Daeschlein et al, ; Fricke et al, ; Kolacyak et al, ; Park et al, ; Plimpton et al, ). Cold atmospheric plasma (CAP) in general is plasma generated at atmospheric pressure and its rotational temperatures (gas temperatures) are close to ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%